The oath on the Bible stored in Justinian's law - Pál Sáry (Journal on European History of Law)
The pagan Romans, like other ancient peoples, placed great importance on the oath. This significant role of oath-taking persisted even after the triumph of Christianity, both in private and public spheres. The act of the oath now took on a Christian character, which found its formal expression in the use of the Bible. The constitutions of Emperor Justinian provide many references to the use of oaths sworn on the Bible. These decrees clearly show that this symbolic legal act, despite its Christian form, in many respects still bore similarities to the old pagan oath formulas and was widely applied.